Social media online privacy in South Africa: The case for blockchain technology innovation - Pinto, Edward Philip Beja Abegao (University of the Witwatersrand, Johannesburg, 2023)
In today's society, it has become nearly impossible to exist without an online presence on some form of social media platform. These platforms have become an integral part of our daily lives, serving as avenues for maintaining relationships and facilitating connections. However, the extensive use of social media exposes users to various privacy concerns and malicious activities. Furthermore, the generation of vast amounts of personal data on these platforms raises questions about data ownership, control, unauthorized data utilization, and constant user activity tracking. Over recent years, concerns surrounding privacy, risks, and exposure on social media have escalated, particularly regarding issues such as data ownership, control, unauthorized data usage, and user activity tracking. Social media users have increasingly expressed the view that platforms are making incremental security improvements without fully addressing users' genuine concerns, which may impact their economic models. This research paper seeks to explore whether blockchain technology can offer a solution to the privacy concerns raised by users of social media platforms. It evaluates the characteristics of blockchain technology in addressing the privacy- related issues associated with traditional social media platforms. The paper begins by establishing a foundational understanding of blockchain, privacy, and the role of social media platforms in today's society. The research identifies the challenges faced by everyday social media users as part of defining the research problem.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Blockchain; Social Media; Online Privacy; UCTD; SDG-9: Industry, innovation and infrastructure